The Radiographic "Air Sign" in Neonatal Mandibular Distraction Osteogenesis. Issue 1 (February 2023) - Safran, Tyler; Alabdulkarim, Abdulaziz; Galli, Rafael; Gilardino, Mirko S.
Timing of extubation on post-mandibular distraction osteogenesis (MDO) surgery is critical, given that at baseline these infants have difficult airways and failed extubation requires either re-intubation of an already complex airway with a fragile, recently osteotomized mandible, or adjunctive airway measures such as CPAP that may apply unwanted pressure to the surgical site. Thus, the goal is to plan extubation when the risk of failure is minimal. Currently, there is a void in the literature addressing the timing of extubation post-MDO and no objective sign of extubation readiness has been elucidated. This study describes a simple clinical pearl to assist in the evaluation of extubation readiness in these patients. Postoperatively, we obtain weekly radiographs to assess distractor stability and advancement, and to assess for the "Air Sign". The Air Sign describes a radiolucent space (air) visualized in the oropharynx on lateral radiographs, likely indicating that the tongue based airway obstruction has been relieved by mandibular advancement.